The Influence of Students Perceptions of Outdoor Study Methods on Students Learning Motivation in Social Studies - Fina Fauziyah; Nadifatul Aulia Wafanda Firamadona; Ajeng Triyani Sholihah; Imam Wahyu Hidayat (STKIP Taman Siswa Bima, 2024)
The purpose of this study was to determine the effect of student perceptions about the use of outdoor study methods on student learning motivation in social studies learning in Probolinggo District. Outdoor study has urgency in improving students' capabilities in both physical and non-physical aspects. This study used a correlational method using a questionnaire as an instrument. The population in this study included all junior high school and MT students in Probolinggo Regency. Purposive sampling was the sampling technique in this study. The sample totaled 91 students: 42 students from SMPIT Permata Kraksaan, 30 students from MTs Al-Husna, and 19 students from SMPN 4 Kraksaan. This study used simple linear regression analysis to analyze the data. The results indicated that students' perceptions of the use of outdoor study methods contributed 45.4% to students' learning motivation, and a total of 54.6% was affected by components that were not the focus of discussion in this study. While the correlation level is 0.674, this is a strong category. In the results of the t test or partial, student perceptions about the use of outdoor study methods have a positive or significant effect on student learning motivation. The value of 8.598> 1.666 and the sign value of 0.000 <0.005 mean that H0 is rejected and Ha is accepted, or student perceptions about the use of outdoor study methods affect student learning motivation.